Evaluating the Effect of Diode Laser Irradiation on Microhardness of Bleached Enamel: An in Vitro Study - Alaa H. Ali; Abduladheem Raouf Sulaiman (University of Mosul, College of Dentistry, 2022)
Aims: To investigate the effect of in-office dental bleaching techniques on the microhardness of enamel and the influence of post bleaching diode laser irradiation on the surface microhardness of bleached enamel. Materials and methods: Forty bovine teeth were prepared and then randomly allocated into two equal groups (n=20) according to bleaching technique as follows: CB: Conventional in-office bleaching technique and LB: Laser-assisted in-office bleaching technique. Each group was subdivided into two subgroups (n=10) according to laser irradiation setting as follows: C2: Conventionally bleached followed by diode laser irradiation at 2-Watt laser, C4: Conventionally bleached followed by diode laser irradiation at 4-Watt laser, L2: laser -assisted bleached followed by diode laser irradiation at 2-Watt laser and L4: Laser-assisted bleached followed by diode laser irradiation at 4-Watt laser. Vickers microhardness was assessed three times for all the specimens: before bleaching, 24 hours after bleaching and finally 24 hours after post bleaching diode laser irradiation. Paired samples t- test and independent samples t- test were utilized for statistical analysis. Results: Both bleached groups exhibited a significant decrease in micro harness after bleaching with no statistically significant differences between them. Post bleaching diode laser irradiation at 2Watt and 4Watt resulted in significant increase in microhardness with no significant difference was evident between them. Conclusions: Diode laser irradiation on bleached enamel had a positive influence on surface microhardness of enamel and it may represent a promising post bleaching treatment modality.